Technical Efficiency Of Agriculture Sector In Shaanxi, China - Li, Yujie (2024)
As living standards improve, the demand for agricultural products increases. However, in Shaanxi Province, China, the agricultural production has not met this increasing demand. In Shaanxi, none of the three agricultural subsectors—crop farming, livestock, and fishery—achieve self-sufficiency. Consequently, the province must rely on other regions or imports to meet its agricultural needs. Increasing input utilisation to boost yield is not considered a sustainable practise. Instead, the Shaanxi government aims to improve agricultural technical efficiency, which means increasing output while maintaining the same level of input. To address this issue, this study investigates the technical efficiency and causes of technical inefficiency in Shaanxi’s each agriculture subsector using Data Envelopment Analysis (DEA) and Tobit regression. In the crop farming subsector in Shaanxi province, there is notable technical inefficiency. It is noteworthy that the cucumber and tomato grown in the glasshouse exhibit decreasing returns to scale and lower technical efficiency scores compared to those cultivated in open fields. This suggests that Shaanxi policymakers should prioritise promoting advanced cultivation methods and invest in improving the efficiency of glasshouse cultivation before increasing the number of glasshouses. Additionally, the cultivation of diverse crops such as carrots, Chinese cabbage, and eggplants has the potential to significantly enhance the overall production and technical efficiency of the Shaanxi’s crop farming subsector. These crops can be promoted for cultivation on new arable land or used to replace less efficient crops.